11=-4(x+1)

Simple and best practice solution for 11=-4(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=-4(x+1) equation:


Simplifying
11 = -4(x + 1)

Reorder the terms:
11 = -4(1 + x)
11 = (1 * -4 + x * -4)
11 = (-4 + -4x)

Solving
11 = -4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
11 + 4x = -4 + -4x + 4x

Combine like terms: -4x + 4x = 0
11 + 4x = -4 + 0
11 + 4x = -4

Add '-11' to each side of the equation.
11 + -11 + 4x = -4 + -11

Combine like terms: 11 + -11 = 0
0 + 4x = -4 + -11
4x = -4 + -11

Combine like terms: -4 + -11 = -15
4x = -15

Divide each side by '4'.
x = -3.75

Simplifying
x = -3.75

See similar equations:

| f=35r^2 | | 3*x-5=34 | | 38x-5=34 | | -6x-3=12-x | | 8-8x=4x-16 | | |x|-4=9 | | 4=-4(x-1) | | 27x+12y-2561=0 | | -12x-15=-123 | | -8+(-4)+5= | | 100+(-30)= | | 88x^2-97x+24=0 | | 88x^2-97+24=0 | | -15+-6= | | 3g+4(-6g+3g)=1-g | | 3(4C-1)-16=10C+3 | | .25(4x+10)=8 | | 18+5T=-3N-12 | | 8y-8=35-7y | | 3y+4+10y-17=14-23y+16-7y | | -5N+10=-3N-12 | | 6y+7-19=7y+13-3y-21 | | A(x-1)-bx=0 | | 8X+58=8X+14 | | -10z+75=-5 | | 2x-10i=8-(4iy) | | 4-C=25 | | 8X+8=5X+7 | | 9*x*x*x+6*x*x=0 | | 15+4y=y | | 125-3x=24+23x | | 2x-10i=8-(4y)I |

Equations solver categories